Evolutionary aspects of oncogenic herpesviruses. Issue 5 (1st October 2000) - Nicholas, J
Abstract : Several of the γ-herpesviruses are known to have cellular transforming and oncogenic properties. The genomes of eight distinct γ-herpesviruses have been sequenced, and the resulting database of information has enabled the identification of genetic similarities and differences between evolutionarily closely related and distant viruses of the subfamily and between the γ-herpesviruses and other members of the herpesvirus family. The recognition of coincident loci of genetic divergence between individual γ-herpesviruses and the identification of novel genes and cellular gene homologues in these genomic regions has delineated a subset of genes that are likely to contribute to the unique biological properties of these viruses. These genes, together with γ-herpesvirus conserved genes not found in viruses outside the family, might be responsible for virus specific pathogenicity and pathogenic effects, such as viral associated neoplasia, characteristic of the subfamily. The presence of the γ-herpesvirus major divergent genomic loci and the apparent increased mutational frequencies of homologous genes (where they occur) within these regions, indicates that these loci possess particular features that drive genetic divergence. Whatever the mechanisms underlying this phenomenon, it potentially provides the basis for the relatively rapid adaptation and evolution of γ-herpesviruses and the diversity of biological and pathogenic properties.